DEVELOPMENT OF DISHES OF DOMESTICATED REINDEER WITH A PROLONGED LIFETIME - E. G. Bogdan; E. G. Turshuk (Современная наука и инновации)
Features of the climate of the Kola Peninsula and the lack of income providing the human body with nutrients and biologically active compounds dictate the need to search for new ingredients and products of functional orientation with the use of raw sources of the Kola Peninsula. Mate